Hemostatic Activity of Cistus creticus Extract in Wistar Albino Rats - Karadag, Ayse Esra; caskurlu, Aysegul; Okur, Mehmet Evren; Guzelmeric, Etil; Okur, Neslihan Ustundag; Tosun, Fatma; Demirci, Fatih (Springernature, 2020)
Aerial part preparations of Cistus creticus L., Cistaceae, are traditionally used in Anatolia as a hemostatic agent. The air-dried aerial parts were extracted with methanol. Gels were prepared, followed by the hemostatic activity evaluation using Wistar albino rats in vivo tail tip amputation model. The chemical characterization of the total extract was performed by high-performance thin-layer chromatography. The methanol extract was loaded to a hydrogel base to complete a concentration of 2.5 and 7.5%. As a result, the 2.5% extract gel was found more effective on both bleeding time and amount. Hyperoside and tiliroside, which may be the components responsible for the hemostatic properties of the analyzed plant material, were dereplicated as major constituents.
Keywords: HPTLC; Topical application; Blood stopper; Coagulating activity; Flavonoid glycoside; Tail bleeding